2017
DOI: 10.1007/s12975-017-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and Clinical Evidence on Ipsilateral Corticospinal Projections: Implication for Motor Recovery

Abstract: Motor impairment is the most common complication after stroke, and recovery of motor function has been shown to be dependent on the extent of lesion in the ipsilesional corticospinal tract (iCST) and activity within ipsilesional primary and secondary motor cortices. However, work from neuroimaging research has suggested a role of the contralesional hemisphere in promoting recovery after stroke potentially through the ipsilateral uncrossed CST fibers descending to ipsilateral spinal segments. These ipsilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 90 publications
2
38
0
Order By: Relevance
“…This neurophysiological deficit was significantly ameliorated by the combined cell/ CTZ therapy, suggesting a novel cell-based rehabilitation strategy, particularly for restoration of damaged neuronal connectivity. Overall, the present investigation supports and successfully demonstrates the importance of activity in the integrity and functional repair of neuronal connections in sensorimotor recovery after brain injury (Alawieh et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…This neurophysiological deficit was significantly ameliorated by the combined cell/ CTZ therapy, suggesting a novel cell-based rehabilitation strategy, particularly for restoration of damaged neuronal connectivity. Overall, the present investigation supports and successfully demonstrates the importance of activity in the integrity and functional repair of neuronal connections in sensorimotor recovery after brain injury (Alawieh et al, 2017).…”
Section: Discussionsupporting
confidence: 79%
“…Instead, arm function is closely related to the integrity of contralateral projections. This therefore suggests that control of these proximal arm muscles after stroke is similar to that of distal muscles in which many reports have shown that functional recovery is tightly linked to the integrity of the crossed corticospinal tract (Alawieh et al, 2017;Byblow et al, 2015;Ward et al, 2006). It differs from what has been reported in axial muscles, in which the presence of ipsilateral responses after stroke is related to increased trunk control (Bradnam et al, 2011;Turton et al, 1996;Misawa et al, 2008;Tsao et al, 2008;Matthews et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…Recovery from motor stroke depends upon the presence of functional connections between the cortex and the spinal cord (Byblow et al, 2015;Ward et al, 2006;Netz et al, 1997;Lemon, 2008b). However, the relative role and importance of connections from the lesioned hemisphere versus those from the non-lesioned hemisphere is still unclear (Buetefisch, 2015;Bradnam et al, 2013;Alawieh et al, 2017;Dodd et al, 2017). In rodent models a large body of evidence has shown that recovery following a cortico-subcortical lesion on one side is accompanied by intraspinal sprouting of connections from pathways originating from the non-lesioned hemisphere (Rouiller et al, 1991;Krakauer et al, 2012;Biernaskie et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in terms of clinical significance, the role of ipsilateral (contralesional) corticospinal projections in motor recovery remains unclear. 35) Clinical severity in the initial phase of stroke is another important determinant of long-term outcome. 3,36,37) We previously reported that the National Institutes of Health Stroke Scale score 38) during the acute phase can predict the extent of FIM-motor recovery.…”
Section: Discussionmentioning
confidence: 99%